Property Rights to Client Relationships and Financial Advisor Incentives - CLIFFORD, CHRISTOPHER P.; GERKEN, WILLIAM C. (Journal of Finance, 2021)
ABSTRACT We study the effect of a change in property rights on employee behavior in the financial advice industry. Our identification comes from staggered firm‐level entry into the Protocol for Broker Recruiting , which waived nonsolicitation clauses for advisor transitions among member firms, effectively transferring ownership of client relationships from the firm to the advisor. After the shock, advisors appear to tend to client relationships more by investing in client‐facing industry licenses, shifting to fee‐based advising, and reducing customer complaints. Our findings support property rights based investment theories of the firm and document offsetting costs to restricting labor mobility.